The effects of blood pressure components on cardiovascular events in a Korean hypertensive population according to age and sex: A nationwide population-based cohort study. Issue 33 (August 2019) - Kang, Eungyu; Lee, Seulbi; Ha, Eunhee; Oh, Hyung Jung; Ryu, Dong-Ryeol
Abstract : Abstract: There is no known study regarding the usefulness of each blood pressure (BP) component based on stratification by age and sex for predicting cardiovascular (CV) events among hypertensive populations without chronic kidney disease (CKD) or diabetes mellitus (DM). This study was performed to investigate the association of BP components and CV events in a Korean hypertensive population according to age and sex. A total of 22, 853 Korean hypertensive participants without CKD and DM were stratified into six groups according to age [40–49, 50–59, and 60 years or older] and sex. In each group, multivariate Cox proportional regression analysis was performed to reveal the associations of BP components [systolic BP (SBP), diastolic BP (DBP), mean arterial pressure (MAP) and pulse pressure (PP)] with CV events. The increase in PP and decrease in DBP were significantly associated with increase of CV events in males, but neither BP component was significantly associated with risk of CV events in females. When subjects were stratified by age and sex, an increase of SBP or PP was significantly related to the increased risk of CV events in 40's male group, and only the elevation of PP was significantly associated with increase in incidence of CV events in 50's male group, while a decrease in DBP was significantly associated with increased risk of CV events in older male group. In addition, there were no the significant associations with the incidence of CV events in MAP, after stratification according to age and sex. In conclusion, this study suggests that, in hypertensive populations, BP management may need to be performed after full consideration of age and sex.